2018
DOI: 10.1038/s41598-018-30390-0
|View full text |Cite
|
Sign up to set email alerts
|

Neural network identification of people hidden from view with a single-pixel, single-photon detector

Abstract: Light scattered from multiple surfaces can be used to retrieve information of hidden environments. However, full three-dimensional retrieval of an object hidden from view by a wall has only been achieved with scanning systems and requires intensive computational processing of the retrieved data. Here we use a non-scanning, single-photon single-pixel detector in combination with a deep convolutional artificial neural network: this allows us to locate the position and to also simultaneously provide the actual id… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
54
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 22 publications
0
54
0
1
Order By: Relevance
“…The choice of the most suitable approaches depends primarily on the complexity of the computational model, as well as the computational budget available (i.e., the expected processing time, data storage limitations, and the desired quality of the information extracted). Supervised machine learning (including deep learning) approaches are particularly well suited for applications where a sufficient quantity of ground truth data or reference data is available (85)(86)(87)(88). Such methods rely on a twostage process, which consists of the training stage and the test stage.…”
Section: Computational Methods In the Photon-starved Regimementioning
confidence: 99%
“…The choice of the most suitable approaches depends primarily on the complexity of the computational model, as well as the computational budget available (i.e., the expected processing time, data storage limitations, and the desired quality of the information extracted). Supervised machine learning (including deep learning) approaches are particularly well suited for applications where a sufficient quantity of ground truth data or reference data is available (85)(86)(87)(88). Such methods rely on a twostage process, which consists of the training stage and the test stage.…”
Section: Computational Methods In the Photon-starved Regimementioning
confidence: 99%
“…The return signal from each voxel is simulated and the voxel shapes/number are then varied in a loop until the difference between the simulated and measured signals is minimised. Caramazza et al, have also demonstrated that is possible to use a deep learning approach to correctly retrieve both position information and the identity of a person hidden behind an obstacle [94]. The method relies on the use of a 32x32 SPAD array camera that is used as an array of 1024 independent, single pixel SPADs.…”
Section: Gated Detection Continuous Illumination and Deep Learningmentioning
confidence: 99%
“…Over the past several years, single-photon sensitive detectors have been used to observe laser propagation in air [27,28], to detect objects hidden from the line-of-sight [29][30][31][32][33], and to image in the presence of scattering media [34][35][36][37][38][39][40]. In particular, progress is being made in the development and implementation of SPAD detectors in the form of dense pixel arrays [41][42][43][44].…”
mentioning
confidence: 99%